Risk Assessment and Spatial Migration Patterns of Compound Flood and Derived Landslide Disasters in Guangzhou,China - LI Xiaodi; ZHONG Ming; LI Xueyou (Renmin Zhujiang)
Compound floods and derived landslide disasters are frequent in estuaries under the influence of high-intensity localized heavy rainfalls and tidal level top support.This paper proposes a comprehensive method for risk assessment and spatial migration patterns of compound flood and derived landslide disasters.Meanwhile,taking Guangzhou as the study area,it constructs the index system for risk assessment of compound floods and derived landslide disasters in the city.Additionally,the weighted comprehensive evaluation method is adopted to assess the risk of multi-source compound disasters,and the spatial risk distribution pattern of the above-mentioned three types of disasters and the migration law of the disaster risk are explored based on the standard deviation ellipse method.The results are as follows:① 52.81% areas of Guangzhou are medium-high risk and high-risk ones,and the risk of composite floods and derived landslide disasters as a whole presents the characteristics of high risk in the northeast and low risk in the southwest,among which the risk of Conghua District and Zengcheng District is higher.Thus,disaster prevention and mitigation measures should be taken to reduce the disaster risks in the above areas.② The center of gravity of the risk of heavy rainfall flooding-composite flooding-composite flooding and derived landslide hazards first moves to the southwest and then to the northeast,and the disaster risk shows a southwest-northeast distribution pattern,with the first enhanced and then gradually weakened aggregation effect of disaster risks.The results can provide a scientific basis for the risk decision-making of compound disasters and disaster prevention planning.